Sustainable Zakat Empowerment Model for Productive Business at Zakat Institutions in West Java Province - Nurhasanah, Neneng; Saripudin, Udin; Ihwanudin, Nandang; Taufiq Rahman, Muhammad Ridha; Fathurrahman, Muhammad Rifqi; Fadhilah, Salma Nurul (KnE Social Sciences, 2023)
The management of Productive Zakat as an alternative solution to the problem of poverty in Indonesia has been an ongoing effort. The Government of Indonesia has shown its commitment to this initiative through normative policies, such as PMA Number 31 of 2019, which outlines the terms and procedures for calculating Zakat Mal and Zakat Fitrah and utilizing Zakat for productive business, based on Law number 23 of 2011 concerning Zakat Management. However, existing regulations have not addressed the technical aspects of how the distribution of Productive Zakat should be carried out to effectively achieve its main goal of empowering those classified as Mustahik in a sustainable manner. This study aims to describe and analyze the model of productive zakat utilization in empowering a sustainable community economy in West Java Province. The research adopts a qualitative method with an analytical descriptive approach. The study concludes that the productive zakat utilization model should be comprehensive and integrative in three ways. Firstly, it should involve the regulation of zakat in conjunction with infaq, shadaqah, and waqf. Secondly, there should be a focus on developing a reliable and capable human resource team for managing the zakat, comprising of amil (collectors) and assistants. Thirdly, the model should emphasize enhancing the intellectual capacity (knowledge and skills), mentality, and spirituality of the mustahiq as the beneficiaries. Keywords: model, zakat utilization, productive business